Formation of Mackenzie Delta Frontier Culture - Honigmann, John J. (Anthropologica, 2022)
In 150 years of intense acculturation and heavy migration, a local frontier culture that is shared by many native people came into existence in the western Canadian Arctic. The frontier culture consists of outdoor-type activities and appurtenances, and it also consists of a readiness to neutralize particular norms and values of the mainstream Canadian culture, particularly those related to formal organization, use of alcohol, and the police. Frontier culture in Inuvik is a symbol through which native people may assert their native identity by following a relatively distinctive way of life.